Enterprises Teori: Sebuah Kajian Teoritis - Muhammad Fahreza Sihombing; Naswa Aprillia Putri; Nazwa Adinda; Siti Sri Wahyuni; Jufri Darma (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines Enterprise Theory in accounting, which emphasizes that companies are accountable not only to shareholders but also to all stakeholders, including employees, the government, society, and the environment. Using a qualitative approach through a systematic literature review based on the PRISMA protocol, this study analyzes the development, implementation, and challenges of applying this theory. The findings reveal that Enterprise Theory emerged in response to the limitations of Proprietary Theory and Entity Theory, which primarily focus on shareholders' interests. This theory highlights transparency and accountability in financial reporting by considering the distribution of value-added income. However, its implementation still faces challenges, such as the absence of binding regulatory standards, difficulties in measuring corporate social contributions, and differing stakeholder perceptions. These findings underscore the importance of integrating social and environmental aspects into modern accounting practices to help companies develop more sustainable business strategies that prioritize the well-being of all stakeholders.